IASI observations of sulfur dioxide (SO2) in the boundary layer of Norilsk. Issue 7 (7th April 2014) - Bauduin, Sophie; Clarisse, Lieven; Clerbaux, Cathy; Hurtmans, Daniel; Coheur, Pierre‐François
Abstract: Norilsk is one of the most polluted cities in the world, largely because of intense mining of heavy metals. Here we present satellite observations of SO2 in a large area surrounding the city, derived from 4 years of measurements from the Infrared Atmospheric Sounding Interferometer (IASI), the nadir thermal infrared (TIR) sounder onboard the MetOp platforms. TIR instruments are conventionally considered to be inadequate for monitoring near‐surface composition, because their sensitivity to the lowest part of the atmosphere is limited by the thermal contrast between the ground and the air above it. We demonstrate that IASI is capable of measuring SO2 (here as a partial column from 0 to 2 km) in Norilsk, thanks to the large temperature inversions and the low humidity in wintertime. We discuss the influence of thermal contrast and of surface humidity on the SO2 retrieved columns and estimate the retrieval errors. Using a simple box model, we derive the yearly total emissions of SO2 from Norilsk and compare them to previously reported values. More generally, we present in this work the first large‐scale demonstration of the capability of space‐based TIR sounders to measure near‐surface SO2 anthropogenic pollution. Key Points: The capability of IASI to probe boundary layer SO2 is demonstrated 4 years of near‐surface SO2 columns are retrieved above Norilsk The first satellite measurement of SO2 above Norilsk for the winter is reported